Conscience on trial : the fate of fourteen pacifists in Stalin's Ukraine, 1952-1953 - Kuromiya, Hiroaki (University of Toronto Press, 2012)
"Conscience on Trial reveals the startling story, kept secret for sixty years, of ordinary citizens caught up in the elaborate machinery of political terror in Stalinist Ukraine. In 1952, fourteen poor, barely literate Seventh-Day Adventists living on the margins of Soviet society were clandestinely tried for allegedly advocating pacifism and adhering to the Saturday Sabbath. The only written records of this trial were sealed in the KGB archives in Kiev, and this harrowing episode has until now been unknown even within the Ukraine. Hiroaki Kuromiya has carefully analyzed these newly discovered documents, and in doing so, reveals a fascinating picture of private life and religious belief under the atheist Stalinist regime. Kuromiya convincingly elucidates the mechanism of the Soviet secret police and explores the minds of non-conformist believers -precursors to the revival of dissidence after Stalin's death in 1953"--Publisher's website.